1974
DOI: 10.1073/pnas.71.5.1748
|View full text |Cite
|
Sign up to set email alerts
|

Non-Selective Inhibition of Transformed Cell Growth by a Protease Inhibitor

Abstract: The protease inhibitors N-tosyl-L-phenylalanylchloromethyl ketone (TPCK) and N-tosyl-Llysylchloromethyl ketone (TLCK) have previously been shown to selectively inhibit growth of simian virus 40-transformed cells, suggesting that proteolytic enzymes play a role in loss of cellular growth control following viral transformation. In contrast, this study shows that TPCKmediated growth inhibition is non-selective, since the growth of both simian virus 40-transformed and untransformed 3T3 cells is similarly reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
1

Year Published

1975
1975
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…It has been suggested that protease inhibitors suppress cell growth by inhibiting protein synthesis directly (31). However, Grayzel et al (20) demonstrated that TLCK significantly inhibits lymphocyte transformation without a major effect on protein synthesis.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that protease inhibitors suppress cell growth by inhibiting protein synthesis directly (31). However, Grayzel et al (20) demonstrated that TLCK significantly inhibits lymphocyte transformation without a major effect on protein synthesis.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier workers studied the effects of protease inhibitors such as 5-amino-L-1-tosylamidopentyl chloromethyl ketone ("tosyllysyl chloromethyl ketone," TLCK) and L-1-tosylamido-2-phenylethyl chloromethyl ketone (TPCK) on growth of normal and transformed cells, in particular the suppression of contact inhibition (1)(2)(3). However, it was found that the growth-inhibiting effect was due, in large part, to the suppression of macromolecular synthesis (4). A highly specific inhibitor with fewer side effects is required for detailed investigation of the function of proteases in eukaryotic cells.…”
mentioning
confidence: 99%
“…As S6K1 mediates important events for cell growth and proliferation (32)(33)(34), the immunosuppressant activity of rapamycin may be due, at least in part, to its inhibition of S6K1. To more fully understand the biological role of S6K1, we previously evaluated the effect of the enzymatic inhibitors N-␣-tosyl-L-phenylalanyl chloromethyl ketone (TPCK) and N-␣-tosyl-L-lysyl chloromethyl ketone (TLCK) on S6K1 activation given their known anti-proliferative and anti-tumorigenic capacity (35)(36)(37)(38)(39)(40). Interestingly, like rapamycin, TPCK (and less potently, TLCK) inhibited the activation of S6K1 by multiple agonists.…”
mentioning
confidence: 99%